2021
DOI: 10.1161/circulationaha.121.055009
|View full text |Cite
|
Sign up to set email alerts
|

Late Outcomes of the RAPID-TnT Randomized Controlled Trial: 0/1-Hour High-Sensitivity Troponin T Protocol in Suspected ACS

Abstract: Background: High-sensitivity troponin assays are increasingly being adopted to expedite evaluation of patients with suspected acute coronary syndromes. Few direct comparisons have examined whether the enhanced performance of these assays at low concentrations leads to changes in care that improves longer-term outcomes. This study evaluated late outcomes of participants managed under an unmasked 0/1-hour high-sensitivity cardiac troponin T (hs-cTnT) protocol compared with a 0/3-hour masked hs-cTnT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…On a population level, initial data on hsTn testing in Ontario (April 2013 to March 2017) were associated with lower MI, angina, and all-cause hospitalization during a time before the algorithms tested in this study were widely used [21]. These findings in Ontario are in agreement with the RAPID-TnT findings, where the standard protocol missed fewer outcomes as compared to the 0/1 h algorithm [8].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On a population level, initial data on hsTn testing in Ontario (April 2013 to March 2017) were associated with lower MI, angina, and all-cause hospitalization during a time before the algorithms tested in this study were widely used [21]. These findings in Ontario are in agreement with the RAPID-TnT findings, where the standard protocol missed fewer outcomes as compared to the 0/1 h algorithm [8].…”
Section: Discussionsupporting
confidence: 80%
“…However, not all studies have supported the safe rule-out or possible discharge of patients from the ED being assigned to the rule-out arms or low-risk categories with these shorter testing algorithms [6,7]. A recent randomized control trial assessing the European Society of Cardiology (ESC) 0/1 h algorithm further questions the safety of these algorithms as it did not reduce cardiovascular death or MI over the long term (2.7% composite outcome with standard protocol versus 3.3% with 0/1 h protocol; p < 0.001) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of troponin release dictate that the levels observed in the early acute phase are closely dependent on the time of myocardial ischemia. 2 The O2B time was reported to be associated with troponin elevation, though only modestly. 20 , 21 The determination of the ischemic time based on diseases and medication histories can be problematic for some patient groups (eg, older individuals, women, and diabetic individuals) who are more likely to present with atypical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that performing an in-practice evaluation of a 0/1-hour high-sensitive cardiac troponin T protocol embedded in emergency department care enabled a more rapid discharge of patients with suspected acute coronary syndrome (ACS) 1 but did not reduce ischemic events over a 12-month follow-up. 2 Baseline cardiac troponin I (cTnI) levels are frequently measured in an emergency department for an evaluation of suspected ACS, 3 but doing so not a part of the formal diagnostic criteria. The release of cTnI exhibits predictable kinetics in the acute onset of an ST-segment elevation myocardial infarction (STEMI), and peak levels of cTnI are associated with both the ischemic quantity and the time of myocardium at risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, follow-up at 1 year demonstrated an increase in both subsequent myocardial infarction and death in patients with low troponin concentrations identified by the hs-cTnT assay and randomised to the 1-hour strategy compared with the 3-hour pathway using the 99th centile. 28 The explanation for these unexpected findings is not clear, but they highlight the importance of conducting adequately powered studies that evaluate both the effectiveness and safety of implementing early rule-out pathways. Furthermore, one other before and after study has evaluated the implementation of an early rule out pathway with hs-cTnT demonstrating a reduction in hospital admissions with no excess in adverse events.…”
Section: Discussionmentioning
confidence: 99%